Risk Management of Koi (Cyprinus carpio) Hatchery Production in Kediri Regency Using the House of Risk Approach - Erlin Dwi Wardani; Riski Agung Lestariadi; Abdul Wahib Muhaimin; Silvana Maulidah; Deana Aulia Juvitasari (Journal of Aquaculture and Fish Health, 2025)
Koi fish aquaculture sector is closely tied to risk. Various factors, such as delays and uncertainties in delivering feed, infections, and pests affecting the koi fish due to irregularities in pond cleaning, delays and improper feeding, and extreme weather conditions, can lead to the death of fish. It is crucial to monitor the increasing risks diligently, as inadequate risk management procedures can lead to losses and potentially disrupt the growth of the industry. The purposes of this risk management on koi fish hatchery production are: 1). Identify and define risk events and risk agents in koi fish farming production in Kediri Regency, 2). Analyze risk events and risk agents in the production of koi fish in Kediri Regency. 3). Analyzing risk management in koi fish aquaculture in Kediri Regency. The proportional sampling method was used to choose the research sample. The House of Risk (HOR) data analysis method was employed in this study to analyze data. Based on the data analysis, a total of 17 risk events were identified in the four processes of koi fish seed production, which consist of risk events in the pond preparation process, risk events in the spawning process, risk events in the maintenance process, and risk events in the harvesting process. These risk events are caused by 33 risk agents.